Evaluating Strategic Alternatives in the Indonesian Pharmaceutical Industry: A QSPM-Based Study of PT Darya-Varia Laboratoria Tbk - Santoso, Satrio Ayom; Setiawati, Riska Ayu (Jurnal Manajemen dan Inovasi (MANOVA), 2026)
Objective – This research aims to evaluate the strategic alternatives available to PT Darya-Varia Laboratoria Tbk by analyzing internal and external strategic factors that influence competitiveness in the Indonesian pharmaceutical industry. The study focuses on determining the most appropriate strategic direction using the Quantitative Strategic Planning Matrix (QSPM). Design/methodology/approach – This study employs a qualitative–quantitative strategic analysis approach using tools such as PEST, Porter’s Five Forces, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), SWOT analysis, IE Matrix, and the Grand Strategy Matrix. The QSPM model is then applied to quantify and compare the attractiveness of alternative strategies, enabling the identification of the most optimal strategic choice for the company. Findings – The analysis shows that PT Darya-Varia operates in a competitive and highly regulated pharmaceutical market influenced by technological advancements, rising health awareness, and strong market rivalry. Internally, the company displays strong brand presence and operational capabilities, yet faces weaknesses such as reliance on imported raw materials. QSPM results identify Product Development as the most attractive strategic alternative, highlighting the importance of adopting advanced technologies such as AI based formulation, nanotechnology, and biotechnology to strengthen competitive advantage. Research limitations/implications – This study focuses on a single case within Indonesia’s pharmaceutical sector, which may limit generalizability. Future research is encouraged to examine similar strategic evaluations in different pharmaceutical companies or across other emerging markets. Additional variables such as digital transformation, supply chain resilience, or post-pandemic market shifts may further enrich strategic insights. Practical implications – The findings provide managerial guidance for PT Darya-Varia and similar companies to prioritize innovation driven product development to enhance competitiveness. Firms are encouraged to invest in technology based R&D, improve supply chain independence, and align strategic initiatives with industry trends to maintain long-term market strength. Originality/value – This research integrates multiple strategic frameworks with QSPM to quantitatively determine the most suitable strategic direction for a leading pharmaceutical company in Indonesia. The study contributes by demonstrating how technology-driven product development can serve as a key strategic lever in a competitive and rapidly evolving industry landscape.